Factors Determining Stock Indices In Asean Countries - Nursyamsiyah; Tri Kunawangsih Purnamaningrum; Yohanis Hans (PT. INOVASI TEKNOLOGI KOMPUTER, 2026)
This study aims to examine and analyze the effect of GDP per capita, inflation, interest trates, and the local currency exchange rate against the US dollar and the Shanghai stock index on the stock price index, with interest rates as a moderating variable in ASEAN during the 2014 – 2023 period. The sampling method used was purposive sampling, and six countries were obained with a total of 720 observational data points. The analysis method used was Moderated Regression Analysis (MRA) with the Eviews application. The results show that GDP per capita, inflation, and the exchange rate have a positif and significant effect on the stock price index,. Meanwhile, inflation has a negative and significant effect on the stock price index and the Shanghai stock index has a positive but not significant effect on the stock price index. Interest rates are able to moderate the effect of GDP per capita, inflation and the exchange rate on the stock price index. However, interest rates are not able to moderate the effect of the Shanghai stock index on the stock price index in ASEAN countries. This indicates the importance and necessity for lokal authorities to regulate macroeconomic dynamics on the stock price index in ASEAN. As well as the need to increase the integration of China’s financial market with ASEAN’s financial markets to enhance market integration and efectiveness